Nuno Júdice : a poesia como matéria-emoção - Larica, Jacqueline Buzan (2008)
Analysis about three poetic work of Nuno Júdice, Teoria Geral do Sentimento(1999), Cartografia de Emoções(2001) e Geometria Variável(2005), rereading the Romantism taking a view of the contemporany portuguese poetic. So, to come to this conclusion, developed reflexions about the romantism like a historical, social aond spiritual moviment, projecting the subjectivism like the force of expression of the artist. Trying to show like the contemporany poet reexamine the romantic rhetoric, making texts using important liric voices of the romantism. It's also an object of discussion the scenary developed in the work of Michel Collot, and the boundaries of the romantic lirism in Nuno Júcide's poetry and the language defines itself like matter-emotion